Awareness and Willingness to Pay for Community Based Health Insurance Scheme in North-Western Nigeria (Bangladesh Journal of Medical Education, 2018)
There is a need for the communities to develop their health financing system, most especially those that were not covered by the National Health Insurance Scheme (NHIS). This will give the people an opportunity to finance their medical care which in turn would alleviate financial burden at the point of treatment. Therefore, this study is aimed to determine the level of awareness for Community Based Health Insurance Scheme (CBHIS) among communities and to measure the degree of willingness to pay for the scheme in Katsina, North-Western Nigeria. Semi structured interviewer-assisted questionnaires were used to collect information from the respondents. Statistical analyses were performed using SPSS version 20.0. The results indicates that majority of the respondents attained tertiary level of education (68.3%) and 81.1% were employed. About 74.2% were earning more than the Nigerian minimum wage N18, 000 (≈$59). About 52.2% of the respondents were aware of the CBHIS. And 81% were willing to pay for premium while 62.2% will pay between N 1, 000 – 5, 000 (≈$3.3- $16.4). There was strong significant relationship between monthly income and knowledge of CBHIS (p = < 0.0001). However, gender and educational level were not significantly associated with the knowledge of CBHIS. Awareness about CBHIS was not sufficiently adequate but a significant number of the respondents were willing to pay for CBHIS after learning about the scheme. Factors such as level of education and income levels were found to have positive effect on willingness to pay.Bangladesh Journal of Medical Education Vol.9(2) 2018: 19-23